P-wave duration and atrial fibrillation recurrence after catheter ablation, a systematic review and meta-analysis. (19th May 2022) - Koutalas, E; Intzes, S; Zagoridis, K; Symeonidou, M; Spanoudakis, E; Arya, A; Dinov, B; Dagres, N; Hindricks, G; Bollmann, A; Kanoupakis, E; Kochiadakis, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) is a global health problem with high morbidity and mortality. Catheter ablation (CA) can reduce AF burden and symptoms, but AF recurrence (AFr) remains an issue. Simple AFr predictors like P-wave duration (PWD) could help improve AF therapy. Purpose: This updated meta-analysis reviews the increasing evidence for the association of AFr with PWD and offers practical implications. Methods: Publication databases were systematically searched and cohort studies reporting PWD and/or morphology at baseline and AFr after CA were included. Complete interatrial block (cIAB) was defined as PWD≥120 ms and biphasic morphology in inferior leads. Random-effects analysis was performed using the Review Manager 5.3 and R programs after study selection, quality assessment and data extraction, to report odds ratio (OR) and confidence intervals (CI). Results: Among 4175 patients in 22 studies, 1138 (27%) experienced AFr. Patients with AFr had longer PWD with a mean pooled difference of 7.8 ms (19 studies, p<0.001)(Figure 1). Pooled OR was 2.04 (1.16-3.58) for PWD>120 ms (13 studies, p=0.01), 2.42 (1.12-5.21) for PWD>140 ms (2 studies, p=0.02), 3.97 (1.79-8.85) for cIAB (6 studies, p<0.001) and 10.89 (4.53-26.15) for PWD>150 ms (2 studies, p<0.001)(Figure 2). There was significant heterogeneity but no publication bias detected. Conclusion: PWD is an independent predictor for AF recurrence after LA ablation. The AFr risk is increasing exponentially with PWD prolongation. This could facilitate risk-stratification by identifying high-risk patients (cIAB, PWD>150 ms) and adjusting follow-up or interventions.